Tahaddiyat wa furas : muhawarat fi ahwal al-fikr wa al-siyasah'inda al-'Arab wa al-Muslimin - al-Marzouki, Abu Ya'rub (Dimashq : Dar al-Farqad, 2008)
Islamic philosophy; Muslims; intellectual life; 21st century
Keywords: Knowledge, Theory of (Islam); Islamic philosophy; Islam -- 21st century; Muslims -- Intellectual life; Arabs -- Intellectual life